Behçet’s Disease: The Clinical and Demographic Characteristics of 406 Patients - Merih SOYLU; Hande TAYLAN ŞEKEROĞLU; Elif ERDEM; Nihal DEMİRCAN (Archives of Rheumatology, 2012)
Objectives: In this study, we aim to describe and investigate the demographic and clinical features, prognostic factors, ocular, and systemic manifestations of the patients with Behçet’s Disease. Patients and methods: The study included 406 patients (306 males, 100 females; 36.1 years; range 12 to 76 years) who met the classification criteria of the International Study Group for Behçet’s Disease. The clinical and demographic characteristics including age at onset, sex, type of ocular involvement, visual acuity, systemic manifestations, and initial signs, and treatment modalities were reviewed. Results: The mean age at onset was 27.6±7.2 years in male patients and 29.0±9.3 years in females. There were no significant differences between both sex in terms of the frequency of ocular involvement (68.9% in male, 65.0% in female, p=0.163) and bilaterality of the ocular involvement (56.2% in male and 53.0% in female, p=0.67). The most common initial presenting manifestation of the disease was oral aphthous ulcer which was seen in 71.9% of the patients, followed by ocular involvement (23.4%). The leading clinical features were oral aphthous ulcers (100%), followed by genital ulcers (82.8%) and ocular manifestations (80.3%). HLA-B51 was positive in 170 of 372 patients (45.7%). HLA-B51 positivity had no effect on the frequency and severity of the ocular inflammatory episodes. Of 306 males, 141 (46.1%) and of 100 females 29 (29.0%) had severe ocular episodes, while 34.6% (n=106) of males and 21% (n=21) of females had frequent ocular involvement. Males had more frequent (p=0.03) and more serious (p=0.015) ocular inflammatory episodes than females. Cyclosporine A was the most commonly preferred agent for patients with frequent episodes (24.3%; p=0.019). Conclusion: Ocular involvement in Behçet’s disease is significantly more frequent and severe in men. The main prognostic criteria affecting the visual acuity are the severity and frequency of ocular involvement.